Formulasi Salep Ekstrak Etanol Daun Tapak Kuda (Ipomoea pes-caprae) Dan Uji Efektivitasnya Terhadap Luka Terbuka Pada Punggung Kelinci - Muthalib, Eka Mulya; Fatimawali, Fatimawali; Edy, Hosea Jaya (PHARMACON, 2013)
ABSTRACT Palm horse weevil contains medicinal properties that are useful in the process of wound healing. The purpose of this study is to to examine formulate an ointment of palm horse (Ipomoea pes-caprae (L) Sweet) weevil extract and to test the ointment to heal open wound on the skin of rabbits. This study is experimental descriptive in the laboratory. Palm horse weevil extracts used in the manufactured of ointment formulation 10%, 15 % and 20 %. The results showed that the palm horse weevil formulation meets the ointment test requirement according, making ointment formulation using cassava tuber extract used as 5 rabbits. Divided into 5 treatment gropus, namely, test the ointment treatment group, negative control group (basic ointment) and positive control group (chloramphenicol ointment). Observed the healing effects for 7 days. The results showed that from day-1 to day-7 observations burns suffered diminution in diameter. It was concluded that concentration of 10 % cassava extract ontment has healing effect and increasing the concentration of 15 % and 20 % contained showed more effective and speed up the healing process. Keywords : Extract leaf palm horse , ointment, wound healing, rabbit.